2017
DOI: 10.25115/ejrep.v4i8.1179
|View full text |Cite
|
Sign up to set email alerts
|

Actividades extraescolares y rendimiento académico en alumnos de Educación Secundaria

Abstract: Introducción. En el presente trabajo estudiamos la influencia que pueden ejercer las actividades extraescolares (escolares y/o deportivas) en el rendimiento académico de alumnos de 1º y 2º de Educación Secundaria Obligatoria (ESO).Método. Seleccionamos aleatoriamente 12 centros educativos de la ciudad (9 públicos y 3 privados) asignando de forma aleatoria a los alumnos participantes (222 alumnos) a dos grupos, en función de si han realizado o no actividades fuera del horario escolar. De esta forma, en el prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 6 publications
0
7
0
15
Order By: Relevance
“…Activity-related stress, whose associated factors are classified in two general categories-activity demands (physical, psychological, social or organizational aspects of the activity requiring sustained physical/psychological effort or skills and therefore associated with certain physiological/psychological costs) and activity resources (functional in achieving work goals, reducing activity demands and the associated costs, stimulating personal growth, learning and development)-can also play a role in the risk of developing burnout syndrome (BS) [7][8][9]. Certain personality traits such as a high degree of empathy, high degree of altruism, low self-esteem, constancy in action, tendency to emotional over-involvement, locus of external control, unrealistic expectations about work, low self-efficacy, and reduced social skills [10][11][12], as well as an excessive concern for body image, perfectionism, impulsivity, competitiveness or tenacity [13], have also been found to play a role in the development of BS. Likewise, sport is often the central element in the lives of athletes, especially those who develop their activity at a competitive level, because it requires high levels of commitment.…”
Section: Introductionmentioning
confidence: 99%
“…Activity-related stress, whose associated factors are classified in two general categories-activity demands (physical, psychological, social or organizational aspects of the activity requiring sustained physical/psychological effort or skills and therefore associated with certain physiological/psychological costs) and activity resources (functional in achieving work goals, reducing activity demands and the associated costs, stimulating personal growth, learning and development)-can also play a role in the risk of developing burnout syndrome (BS) [7][8][9]. Certain personality traits such as a high degree of empathy, high degree of altruism, low self-esteem, constancy in action, tendency to emotional over-involvement, locus of external control, unrealistic expectations about work, low self-efficacy, and reduced social skills [10][11][12], as well as an excessive concern for body image, perfectionism, impulsivity, competitiveness or tenacity [13], have also been found to play a role in the development of BS. Likewise, sport is often the central element in the lives of athletes, especially those who develop their activity at a competitive level, because it requires high levels of commitment.…”
Section: Introductionmentioning
confidence: 99%
“…Following this line of research, studies conducted with students between 9 and 11 years of age have shown that high academic performance or academic achievement improves as the physical condition of the participants increases [10]. Other research [13] has reported a great difference in the academic achievement of students who participate in extracurricular sports compared to those who do not, with better grades achieved by those who participate in sports activities [2,14]. This is consistent with the conclusions of several systematic reviews [9,15] that report strong evidence of a positive relationship between physical fitness and academic performance in longitudinal studies, demonstrating the association between students' physical capacity, cognitive development and academic results.…”
Section: Introductionmentioning
confidence: 91%
“…En la Universidad de la Sabana, ubicada en Bogotá-Colombia, se realizó en el año 2016 una investigación sobre el impacto de los programas extracurriculares en la excelencia académica, esta arrojó varias conclusiones, entre ellas: la participación de los estudiantes del Gimnasio Campestre en el programa extracurricular "Escuelas de Formación" tiene una estrecha y positiva relación con el logro académico, es decir, que los estudiantes que participan en las Escuelas de Formación presentan mejores resultados académicos en comparación con los que no participan (22).…”
Section: Antecedentesunclassified